A call to awaken the Chilean Society of Forest Science - Salas Eljatib, Christian; Promis, Álvaro (BOSQUE, 2020)
While the Chilean Society of Forest Sciences (SOCIFOR) was created by a group of forest-related institutions, its inactivity has wakened its progress. Here, we point out certain shortcomings of SOCIFOR, and propose actions to address them. We suggest increasing the number of members, restructuring its regulatory statutes - modeled on those used by other scientific societies-, taking an active role in the organization of the national forest science congress and editing the Chilean journal of forest science (i.e. Bosque). Strengthening SOCIFOR would help to improve the standing of forest sciences in the country. Our proposal is ambitious, though doable, if the keys come together to achieve a common goal: strengthening forest sciences in Chile.